2017
DOI: 10.1055/s-0037-1605556
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for Ultrasonographic Measurements of the Uterine Cervix in Low-Risk Pregnant Women

Abstract: Objective To define transvaginal ultrasound reference ranges for uterine cervix measurements according to gestational age (GA) in low-risk pregnancies. Methods Cohort of low-risk pregnant women undergoing transvaginal ultrasound exams every 4 weeks, comprising measurements of the cervical length and volume, the transverse and anteroposterior diameters of the cervix, and distance from the entrance of the uterine artery into the cervix until the internal os. The inter-and intraobserver variabilities were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Specifically, it is presumed that attenuation depends on hydration status of the cervix, and that hydration increases as gestation progresses (Bigelow et al, 2008;McFarlin et al, 2015b). This is not unreasonable; recent studies in pregnant women confirm that as pregnancy advances, cervical diameter and volume increase (Andrade et al, 2017) as does surface area (Qian et al, 2016). Interestingly, these observations are not consistent with tissue biopsies, which demonstrate a relatively small difference (3-6%) in hydration between the early (or non-) pregnant cervix and late pregnant cervix (Uldbjerg et al, 1983;Danforth et al, 1974;Petersen and Uldbjerg, 1996;Rechberger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is presumed that attenuation depends on hydration status of the cervix, and that hydration increases as gestation progresses (Bigelow et al, 2008;McFarlin et al, 2015b). This is not unreasonable; recent studies in pregnant women confirm that as pregnancy advances, cervical diameter and volume increase (Andrade et al, 2017) as does surface area (Qian et al, 2016). Interestingly, these observations are not consistent with tissue biopsies, which demonstrate a relatively small difference (3-6%) in hydration between the early (or non-) pregnant cervix and late pregnant cervix (Uldbjerg et al, 1983;Danforth et al, 1974;Petersen and Uldbjerg, 1996;Rechberger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…More medical information was provided by the results of ultrasound examinations. However, both methods had a similar predictive value [32]. In our study, the cervix was not assessed according to the Bishop score due to the subjectivity of this method, emphasized by other authors [33,34].…”
Section: Discussionmentioning
confidence: 66%
“…CLs < 10th centile are at risk of PTB, especially with a decrease in CL after 16 weeks [30] In our study, the results of the ultrasound assessment of the CL and an elastographic examination were analyzed. The evaluation of the cervical length measurement in relation to other parameters is the subject of many studies comparing the palpation with ultrasound examination of the cervix, especially in patients with premature contractions of the uterine muscle and preserved amniotic fluid [31][32][33][34]. Women between 24 and 34 weeks of pregnancy were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of building reference curves that respect the cervical anatomy, we suggest that the most adequate method to measure the cervix is respecting the curvature, however, for short cervix, which is the main factor related to spontaneous PTB, the straight-line measurement for cervical length may be the best strategy. Previous studies have already compared the straight technique with the curved technique [23], as well as the contribution of the volume of the uterine cervix for the diagnosis of short cervix. No technique showed better results compared to the standard technique [24][25][26][27][28][29].…”
Section: Plos Onementioning
confidence: 99%
“…We also observed that the volume of the cervix increased slightly over the course of gestation despite the progressive shortening of the longitudinal measurement of the cervix. In other words, the cervix becomes shorter but wider [23]. Although many studies have shown a correlation between cervical volume and the ability of this measure to contribute to the prediction of the risk of prematurity, none has demonstrated additional benefits in relation to the longitudinal cervical measurement technique [24][25][26][27][28].…”
Section: Plos Onementioning
confidence: 99%